Neo-Naturalistic Drama: a Study of British Drama After 1950 - Sameeul Haq Nazki (International Journal of Integrative Sciences, 2023)
The present paper is an endeavour to show the development of Neo-naturalism as a distinctive dramatic mode of social representation. Neo-naturalism is unanimously seen as a unique appearance of theatricality in the 1950s. In order to understand this Neo-naturalistic drama and its unparallel contribution, it is worthwhile to see how it emanated at a crucial historical juncture. It was a point in time when drama had lost its direction and purpose. Neo-naturalism appeared as a major dramatic model to reverse the inaction and decadence during the second half of the twentieth century. This paper also highlights the role played by John Osborne in being an initiator of this theatricality and taking this Neo-naturalism to a zenith. This Neo-naturalism achieved what was beyond the expectations of the dramatic critics during 1950s. Neo-naturalism can be seen as a force of social transformation and a committed defence against all evils of the society